Living, Breathing Songs: Singing Along with Bob Dylan - Keith, Negus (Center for Studies in Oral Tradition, 2018)
Taking issue with approaches to Bob Dylan’s art that are preoccupied with his lyrics, this article suggests a route into thinking about his music by focusing on how Dylan’s vocal melodies work at the intersection of speech and singing. Drawing on Gino Stefani’s work on popular melodies, this article explores this issue through a discussion of how people sing along with Dylan’s songs at concerts. The discussion focuses on the song “It Ain’t Me Babe,” and examines more general points about the ways in which Dylan’s melodies connect with the everyday lives of his listeners.